ANALISIS PENGARUH UNSUR-UNSUR INTERNAL CONTROL SYSTEM TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (AKIP) (Studi Pada Satuan Kerja Perangkat Daerah Kabupaten Pelalawan) - Aini, Nurniatul; Dp, Emrinaldi Nur; ', Julita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to examine the effect of variables that are included in the elements of the Internal Control System, such as Competence of government officials, financial accountability Applied, Information Technology Utilization, decision authority and obedience to the laws and regulations to Performance Accountability Government. The population in this study were all SKPDs Pelalawan. The Sample in this study was the head of department, chief / head of section and sub-section of financial in SKPD Pelalawam by the number of respondents 86 people from 43 SKPD. Data collection method using a questionnaire. Data were analyzed using analysis methods Partial Least Square (PLS) ver.2.0 with a model inner and outer evaluation models. The results of this research showed : Competence of government officials and Obedience to Laws has a significant positive effect on performance accountability government (AKIP), while the variable application of Information Technology Utilization, financial accountability, and decision authority has no effect on agency performance accountability government (AKIP).Keywords: Performance Accountability Government, Competence government officials, financial accountability Applied, Information Technology Utilization, decision authority, obedience to the laws and regulations.